PENGARUH PUPUK KOMPOS BERBAHAN CAMPURAN LIMBAH CAIR TAHU, DAUN LAMTORO DAN ISI RUMEN SAPI SEBAGAI MEDIA KULTUR TERHADAP KEPADATAN POPULASI SPIRULINA SP. - RAHMAWATI, NURYANI (LenteraBio: Berkala Ilmiah Biologi, 2012)
Most of farmer still use inorganic fertilizer even chemistry on the long term will bad affect to environment because it can?t be recycle to return. Therefore we need a natural alternative fertilizer that didn?t have bad affect to environment but can optimize Spirulina sp. reproduction. It was compost fertilizer materialized by mixture of liquid waste of soybean curd, lamtoro leaf and content of cow rument. This research have a purpose to know the content of  N, P and K substance in compost fertilizer materialized by mixture of liquid waste of soybean curd, lamtoro leaf and content of cow rument ; to know the influence of adding compost to the population solidity of Spirulina sp. ; and to know the relative growth rate of Spirulina sp. population after adding compost fertilizer.This research consist of two stage, the first stage made compost fertilizer materialized by mixture of liquid waste of soybean curd, lamtoro leaf and content of cow rument which is descriptive research. The second stage was the application of compost fertilizer as culture media of Spirulina sp. which is experimental research. This research used The Randomized Block Design (RBD) with 5 factors treatment consentration. The consentration was : 6,412 g/10L;  9,618 g/10L ; 12,824 g/10L dan 16,03 g/10L. Beside that this research was used Urea 0,8 g/10L and TSP 0,3 g/10L as a control. The measured parameter in this research is the population solidity of Spirulina sp. and the relative growth rate of Spirulina sp. population.The result showed that the substance content of N, P and K in compost fertilizer materialized by mixture of liquid waste of soybean curd, lamtoro leaf and content of cow rument that used in this research was high, such as N = 2,64% ; P = 1,56% ; K = 1,17%. The difference of compost fertilizer gived influence to the population solidity of Spirulina sp., expecially in stationary phase. Each of this treatment shows different pattern of growth, also different relative growth rate of Spirulina sp.